contestada

Use the following graph of the function f(x) = 3x^4 − x^3 + 3x^2 + x − 3 to answer this question: What is the average rate of change from x = −1 to x = 0?
A. −6
B. −3
C. 3
D. 6

Respuesta :

9514 1404 393

Answer:

  A.  -6

Step-by-step explanation:

The average rate of change on that interval is given by ...

  m = (f(0) -f(-1))/(0 -(-1)) = f(0) -f(-1)

  m = -3 -(3) = -6

The average rate of change on the interval is -6.

Ver imagen sqdancefan

Answer:

A. -6

Step-by-step explanation:

#CarryOnLearning